Molecular codes for neuronal individuality and cell assembly in the brain - Yagi, Takeshi (Frontiers in Molecular Neuroscience, 2012)
The brain contains an enormous, but finite, number of neurons. The ability of this limited number of neurons to produce nearly limitless neural information over a lifetime is typically explained by combinatorial explosion; that is, by the exponential amplification of each neuron’s contribution through its incorporation into “cell assemblies” and neural networks. In development, each neuron expresses diverse cellular recognition molecules that permit the formation of the appropriate neural cell assemblies to elicit various brain functions. The mechanism for generating neuronal assemblies and networks must involve molecular codes that give neurons individuality and allow them to recognize one another and join appropriate networks. The extensive molecular diversity of cell-surface proteins on neurons is likely to contribute to their individual identities. The cadherin-related neuronal receptors and clustered protocadherins (CNR/Pcdh) is a large subfamily within the diverse cadherin superfamily. The CNR/Pcdh genes are encoded in tandem by three gene clusters, and are present in all known vertebrate genomes. The set of CNR/Pcdh genes is expressed in a random and combinatorial manner in each neuron. In addition, cis-tetramers composed of heteromultimeric CNR/Pcdh isoforms represent selective binding units for cell-cell interactions. Here I present the mathematical probabilities for neuronal individuality based on the random and combinatorial expression of CNR/Pcdh isoforms and their formation of cis-tetramers in each neuron. Notably, CNR/Pcdh gene products are known to play crucial roles in correct axonal projections, synaptic formation, and neuronal survival. Their molecular and biological features suggest that the diverse CNR/Pcdh molecules provide the molecular code by which neuronal individuality and cell assembly permit the combinatorial explosion of networks that supports enormous processing capability and plasticity of the brain.